Peran Kepercayaan Guru-Siswa dalam Optimalisasi Strategi Pendampingan Anak dengan Gangguan Spektrum Autisme di PAUD Inklusi - Tittandi, Nindya Alifia; Hapsari, Sinta Maulida; Tanto, Octavian Dwi (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – Although inclusive education is increasingly implemented, practical insights into effective teaching strategies for supporting children with autism spectrum disorder (ASD) remain limited. This study explores the lived experience of a shadow teacher in applying concrete strategies to support a child with ASD in an inclusive early childhood education setting.Method – A qualitative research design with a phenomenological approach was employed. Data were collected through a semi-structured, in-depth interview with a teacher who had over one year of experience assisting a child with ASD. The data were analyzed using descriptive phenomenological methods to capture essential themes of the teacher’s experience. Findings – The study identified key strategies such as individualized instruction, modified learning objectives, use of reward systems, and ongoing communication with parents, therapists, and school personnel. Consistency across home and school environments, supported by collaborative systems, was found to be essential. Importantly, the development of interpersonal trust between the teacher and the child emerged as a critical factor in the success of individualized strategies—a dimension often underrepresented in current literature. Research Implications – This study provides practical implications for inclusive early childhood education by highlighting the importance of relational, trust-based teaching strategies. While the focus on a single participant limits generalizability, the findings contribute valuable perspectives to teacher training and educational policy development, particularly in relation to supporting children with ASD in inclusive settings.